(untitled) (Global Journal of Management and Business Research, 2017)
Banks are the company which serve the society on the financial services. Banque populaire du Rwanda (BPR) is the one in providing such activity in Rwanda. Different means are provided to consider BPR activities. The main aim to this study is to analyze the financial indicators and business sustainability determinant of predicting future outlook of BPR Ltd during the period 2011 to 2015. BPR improves its services if it is aware of the sustainability index and the financial indicators as well as the relationship between financial indicators and factors of BPR business sustainability. After the employment of techniques in collecting both primary and secondary data on the sample of 83 out of 1606 total population, the financial indicators and business sustainability were analyzed using Bank Analysis Fact sheet (BAFs) and Statistical Package for Social Sciences (SPSS).